2014
DOI: 10.1007/s11046-013-9723-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chemical Composition of Commercial Lemon Essential Oils on the Growth of Candida Strains

Abstract: Candida yeasts are saprophytes naturally present in the environment and forming colonies on human mucous membranes and skin. They are opportunistic fungi that cause severe and even fatal infections in immunocompromised individuals. Several essential oils, including eucalyptus, pine, cinnamon and lemon, have been shown to be effective against Candida strains. This study addresses the chemical composition of some commercial lemon essential oils and their antifungal potential against selected Candida yeast strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
(36 reference statements)
3
23
0
Order By: Relevance
“…Comprehensive analysis illustrates the importance of monoterpenes to antifungal activities and there were differences among different types of Candida strains. The results agree with those of Białon et al [20] who suggested that the antifungal potential of lemon essential oils against Candida yeast strains was related to the high content of monoterpenoids and the type of Candida strains.…”
Section: Resultssupporting
confidence: 92%
“…Comprehensive analysis illustrates the importance of monoterpenes to antifungal activities and there were differences among different types of Candida strains. The results agree with those of Białon et al [20] who suggested that the antifungal potential of lemon essential oils against Candida yeast strains was related to the high content of monoterpenoids and the type of Candida strains.…”
Section: Resultssupporting
confidence: 92%
“…Thus using of these products as therapeutic agents or even cosmetics would require confirmation of their antimicrobial activity (for each production batch). Interesting analysis of differences of chemical composition as well as antifungal activity of commercially available Lemon essential oils has been recently presented by Bialon and coworkers [21]. From 6 tested commercial oils only 4 showed antifungal potential.…”
Section: Discussionmentioning
confidence: 99%
“…[24] These results were subsequently confirmed for the fungicidal action of lemon oil against Candida albicans pathogenic yeasts, wherein the most active antimicrobial was found to be citral. [25] Remarkably, the concentration of the latter oxygenated monoterpene is particularly abundant in the peel of citrus grown (in Sicily) according to organic farming principles. [26] Indeed, the waste lemon peel used to produce the IntPec was obtained by a citrus company in Sicily using only organically grown lemons.…”
Section: Resultsmentioning
confidence: 99%